Clinical characteristics and factors associated with COVID-19-related death and morbidity among hospitalized patients with cancer: a Swedish cohort study. (2nd November 2021) - Ullgren, Helena; Camuto, Angela; Rosas, Sumy; Pahnke, Simon; Ginman, Beatrice; Enblad, Gunilla; Glimelius, Ingrid; Fransson, Per; Friesland, Signe; Liu, Lisa L.
Abstract: Introduction: Cancer patients are considered to have a higher risk of dying and developing severe Coronavirus Disease 2019 (COVID-19). To date, there are few studies including co-morbidities and sociodemographic factors when investigating the outcome of COVID-19 in a cohort of cancer patients. In this study, we analyzed cancer patients that have been hospitalized due to COVID-19 during the first wave of the pandemic in Sweden to investigate the impact of COVID-19 on mortality and morbidity. Patients and methods: We retrospectively collected data on all patients with cancer that were hospitalized due to COVID-19-related symptoms at Uppsala University Hospital and Karolinska University Hospital between 1 March and 31 August 2020. The primary endpoint was COVID-19-related death and the secondary endpoint was to describe COVID-19 severity, defined as symptom severity (grades 0–4) and length of stay (LOS) at the university hospitals. Results: In total, 193 patients were included among which 31% died due to COVID-19 and 8% died of other causes. In a multivariable analysis, older age >70 (OR 3.6; 95% CI [1.8–7.3], p < 0.001) and male gender (OR 2.8 [1.4–5.8], p = 0.005) were factors associated with higher likelihood of COVID-19-related death. Several comorbidities ≥2 (OR 5.4 [2.0–14.3], p = 0.001) was independently associated with COVID-19 severity. Treatment with chemotherapy within 90 days prior to COVID-19 diagnosis were not associated with COVID-19-related death or severity. Conclusion: Factors associated with higher likelihood of COVID-19-related death were older age and male gender. More severe COVID-19 symptoms were seen in patients with multiple comorbidities. We did not see any associations between COVID-19-related death or severity and recent treatment including chemotherapy. In summary, this supports a thorough assessment regarding potential risks with COVID-19 infection in patients with cancer, with a combination of individual risk factors in addition to cancer treatments.